APAKAH FINANCIAL DISTRESS MEMENGARUHI PENGHINDARAN PAJAK? STUDI KASUS PADA PERUSAHAAN PUBLIK DI INDONESIA - Dian Rahmana (Direktorat Jenderal Pajak, 2022)
This research aims to test factors that affect corporate tax avoidance using sample of manufacturing companies listed in the Jakarta Stock Exchange for the year period 2016-2018. It uses SPSS 22 to facilitate moderated regression analyses. The research finds that: (1) profitability has a positive and significant influence on tax avoidance; (2) leverage does not influence tax avoidance; (3) financial distress does not moderate the effect of profitability on tax avoidance; and (4) financial distress moderates the effect of leverage on tax avoidance. The findings implies that the Directorate General of Taxes can partially use profitability as a tool to measure corporate tax avoidance. Whereas leverage can be used in supervising and auditing efforts by first selecting a healthy company because the healthier the company, the greater the influence of leverage on tax gap or corporate tax avoidance.